PROBLEMATIKA GURU DALAM PEMBELAJARAN AKIDAH AKHLAK DI ERA DIGITAL PADA MADRASAH TSANAWIYAH NEGERI 1 KOTA JAMBI - Nurkholiq, Ahmad; Anwar, Khoirul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of digital technology presents new challenges in the teaching of Akidah Akhlak, especially in the formation of students' character and morals. This study aims to analyze the problems faced by teachers in teaching Akidah Akhlak in the digital era at Madrasah Tsanawiyah Negeri (MTsN) 1 Kota Jambi. This study uses a descriptive qualitative approach with data collection techniques through interviews, observations, and documentation. The research results show that learning is still conducted face-to-face by utilizing digital technology as a supporting media for learning. However, teachers face various problems, such as the negative influence of social media on student behavior, the low interest in reading due to excessive use of mobile phones, differences in students' ability to utilize technology, and the limitations of facilities and digital-based pedagogical competence. To address these issues, teachers implement various strategies, such as linking the material to digital phenomena, using methods like lectures, discussions, and Q&A sessions, as well as instilling moral values through habituation and oral evaluations. This research shows that strengthening the role of teachers in wisely utilizing technology is an important factor in shaping the character of students in the digital era.